Mosquito populations originating from nonendemic areas have the potential to transmit recently emerging Japanese encephalitis virus genotype IV - Astri Nur Faizah; Daisuke Kobayashi; Faustus Akankperiwen Azerigyik; Ryo Matsumura; Izumi Kai; Yoshihide Maekawa; Yukiko Higa; Kentaro Itokawa; Toshinori Sasaki; Kris Cahyo Mulyatno; Sri Subekti; Maria Inge Lusida; et al. (Emerging Microbes and Infections)
Japanese encephalitis virus (JEV) genotype IV (GIV) is one of the least common and most neglected genotypes worldwide, having been identified only on a few Indonesian islands until it was recently found to be the cause of outbreaks that occurred in several Australian states in early 2022. Given the limited availability of information, the vector range for JEV GIV remains unknown; thus, understanding this range could prove invaluable for future prevention efforts in new areas. Herein, we experimentally exposed four mosquito colonies originated from various countries with no previous reports of GIV to JEV GIV strain 19CxBa-83-Cv, which was isolated from Culex vishnui Theobald collected in Bali in 2019. At 7 and 14 days post-JEV GIV exposure through a membrane feeding method, mosquito bodies, head–wings–legs, and saliva were harvested for infection, dissemination, and transmission efficiency analyses. The results showed robust transmission efficiencies of the virus by Culex tritaeniorhynchus Giles (∼74%) and Aedes albopictus Skuse (∼52%) from Japan, followed by Culex quinquefasciatus Say from Vietnam (∼35%) and Culex pipiens form molestus from Turkey (∼18%). Although significant differences were observed, we found that the four mosquito species could transmit JEV GIV. The efficiency of biological transmission of this restricted genotype by mosquitoes from various origins suggests that these mosquito species could support localized transmission if the genotype were introduced to their respective areas. This study emphasizes the importance of remaining vigilant and continuing arbovirus surveillance in all locations.